Avaliação da segurança oncológica do lipofilling após tratamento cirúrgico do câncer de mama: revisão sistemática e metanálise - TUKIAMA, Ricardo (2021)
BACKGROUND: In the last decade, autologous fat grafting has increased popularity as a breast reconstructive procedure. One of the major limitations for its widespread use comes from the results of preclinical studies, showing that applying fat grafting to a previous breast cancer site could stimulate the activation of latent cancer cells, creating a favorable environment for disease recurrence. OBJECTIVE: A systematic review and meta-analysis was performed to investigate the impact of fat grafting on breast reconstruction in the risk of locoregional recurrence in patients formerly treated for breast cancer. METHODOLOGY: A systematic review was performed, searching for clinical studies which set a control group up with a prior diagnosis of breast cancer, and with the highest level of evidence designed to assess the oncologic safety of autologous fat grafting as a breast reconstructive procedure, in the electronic databases Pubmed, Embase, Web of Science, and Cochrane. In a pooled analysis of selected studies, the primary outcome was comparing global locoregional recurrence between groups. We performed secondary analyses of locoregional recurrence in subgroups for the type of oncologic surgery (breast-conserving surgery or mastectomy) and histological type (invasive carcinoma or in situ carcinoma). RESULTS: From a total of 598 publications, two independent reviewers performed the screening of studies, according to PRISMA methodology, PICOS strategy, and qualitative assessment of studies using the Q-Coh tool, resulting in the selection of nine matched cohorts with a similar methodology for meta-analysis, including a total of 4247 subjects (1590 subjects who underwent autologous fat grafting, and 2657 control subjects). The average follow-up time was between 64 and 121 months after oncologic surgery for both groups and between 32 and 65 months after the first fat grafting session. Neither of the assessed outcomes had a significant heterogeneity between studies (p-value > 0.10). In pooled quantitative analyses, neither of the outcomes had a statistically significant difference for disease recurrence. For the primary outcome, which compared global locoregional recurrence rates between groups, the incidence rate ratio was 0.92 (95% CI: 0.68 – 1.26; p = 0.62). For subgroup analyses of secondary outcomes, the relative risks for locoregional recurrence for patients undergoing breast-conserving surgery was 0.83 (95% CI: 0.54 – 1.58; p = 0.40), for mastectomy was 0.98 (95% CI: 0.53 – 1.80; p = 0.95), for invasive carcinoma was 0.90 (95% CI: 0.62 – 1.30; p = 0.57), and for in situ carcinoma was 0.58 (95% CI: 0.18 – 1.85; p = 0.35). CONCLUSION: In the present pooled analysis from the outcomes of nine matched cohorts, which currently represent the individual studies with the highest level of evidence on the topic, and including recent studies with a longer follow-up after fat grafting than most prior ones, strengthens the evidence favoring the oncologic safety of autologous fat transfer as a breast reconstructive method.